👤

17.
Write the equation in standard form. Then factor the left side of the equation.

2x2 + 7x = 15


A. (2x – 5)(x + 3) = 0

B. (2x + 3)(x + 5) = 0

C. (2x – 3)(x + 5) = 0

D. (2x + 5)(x – 3) = 0

Answer :

C (2x-3)(x+5). I just know. Please give me the brainliest

Answer:

C. (2x – 3)(x + 5) = 0

Step-by-step explanation:

The equation in standard form should be 2x^2 + 7x - 15 = 0

Factored the expression is (2x - 3)(x + 5).

In order to find the factored portion, you must look for factors of the front number (2) to use in the front of the parenthesis and factors of the last number (-15) to go in the end.  

When we use the ones that we have above, it distributes to the overall end result.  

(2x - 3)(x + 5)

2x^2 - 3x + 10x - 15

2x^2 + 7x - 15

View image Maddymcg408

Go Teaching: Other Questions